Early detection and monitoring of fuel leaks - Huntley, Sharon L. (Cranfield University, 2005)
A novel integrated detection system· has been developed to protect the environment from hydrocarbon fuels leaking from large-scale storage facilities. Over the last decade, land and subsequent groundwater contamination from hydrocarbon fuels has been identified as the major threat to drinking water resources across Europe and the United States. The integrated system developed within this work has two main components: (1) 'Early warning' free-phase fuel leak detection sensors; (2) A novel immunoassay field test for rapid, in situ follow-up analysis of contaminated sites through determination of the extent of the contamination and early indication of dissolved-phase fuel migration. (1) A prototype optical reflectometric device has been developed, in conjunction with state-of the-art data acquisition and relay technology to provide a simple, low-cost hydrocarbons monitoring solution. In extensive field trials, this system has been evaluated as a multiple-array, sub-surface, remote leak detection and monitoring system for early detection of free-phase hydrocarbon contamination. The sensors respond to all. free phase hydrocarbons and can determine plume movement through soil. Preliminary leak information from these sensors can be combined with subsequent, quantitative site analysis using the immunoassay to provide an integrated, highly sensitive and low-cost solution for long term monitoring and analysis. (2) A novel ELISA has been developed for detection of the most controversial fuel oxygenate - \ methyl tert-butyl ether (MTBE), identified as the most major threat to groundwater (and consequently drinking water) resources above any other hydrocarbon contaminant. The ELISA is a classical competitive immunoassay involving free MTBE and a novel antigen consisting of an MTBE analogue covalently bound to BSA. The ELISA was optimised and transposed into a magnetic bead format, the detection range was 0.5-5000 ppm (IC50 5 ppm, assay time 65 minutes). Also detectable are MTBE degradation products TBA, TBF and alternative fuel oxygenates TAME, DIPE and ETBE. MTBE is highly soluble in water and so is an excellent marker for assessing the extent of site contamination. This integrated detection system potential provides a sensitive, cost-effective solution for early detection, analysis and surveillance of petroleum fuel contamination in a range of applications.